Epidural Neostigmine and Clonidine Improves the Quality of Combined Spinal-Epidural Analgesia in Labor: A Randomized, Double-Blind, Controlled Trial. Issue 2 (June 2015) - Boogmans, T.; Vertommen, J.; Valkenborgh, T.; Devroe, S.; Roofthooft, E.; Van de Velde, M.
Abstract : ( Eur J Anaesthesiol . 2014;31(4):190–196)